(untitled) (Bangladesh Journal of Agricultural Research, 2015)
A field experiment was conducted at the farm of Hill Tract Agricultural Research Station, Ramgarh, Khagrachari Hill District during Rabi season of 2010-11 and 2011-12 to determine the optimum sowing time for better yield of green cob as well as fodder of sweet corn (var. BARI Sweet corn-1) in the hilly region. Five sowing dates (November 20, November 30, December 10, December 20 and December 30) were included in the study. During 2010-11, the highest green cob yield was obtained from 20 November sowing (8.43 t/ha) followed by 30 November sowing (7.81 t/ha) and the lowest yield (5.00 ton/ha) from 20 December sowing. During 2011-12, the maximum green cob yield (8.60 t/ha) was also obtained from 20 November, which was statistically identical with that of 30 November (8.03 t/ha), 10 December (7.67 t/ha) and 20 December (8.11 ton/ha) sowing. Average of two years result showed that, the maximum fodder yield (39.99 t/ha) was obtained from 30 November sowing which was at par with that of 20 November sowing. Maximum TSS (Total soluble sugar) value of Sweet corn was obtained from 20 November sowing during 2010-11 and 30 November sowing during 2011-12. Across over two years, 20 November to 30 November sowing was found suitable for sweet corn production in the hilly areas in terms of green cob and fodder yield and also TSS value. Bangladesh J. Agril. Res. 40(1): 61-69, March 2015